Using the Google Drive as a cloud service in a mobile learning - T. I. Chernichkina (Academy of Cognitive and Natural Sciences, 2014)
Research goals: to examine examples of using Google Drive as a service for the implementation of mobile learning technology. Research objectives: to demonstrate how to use modern methods of learning using mobile cloud technologies. Object of research: cloud services in a mobile learning. Subject of research: using the Google Drive as a cloud service in a mobile learning. Research methods used: theoretical - analysis of scientific and methodological literature; empirical - training, monitoring of the learning. Results of the research. This article was considered an example of using Google Drive as a service for the implementation of mobile learning technology. We demonstrate how to use modern methods of mobile learning using cloud technologies. Service is selected in view of availability, ease of implementation and understanding for students. This approach demonstrates the benefits of modern technology together with mobile learning characteristics. The main conclusions and recommendations. To use the new possibilities of mobile learning in the educational process requires organizational, research and methodological work on the implementation of modern policies, forms and methods of mobile learning in the educational process.